A systematic review and meta-analysis of cohort studies on the potential association between NAFLD/MAFLD and risk of incident atrial fibrillation - Zhou, Ben‐Gang; Ju, Sheng-Yong; Mei, Yu-Zhou; Jiang, Xin; Wang, Meng; Zheng, Ai-Jing; Ding, Yan-Bing (Frontiers in Endocrinology, 2023)
Background and objective The association between atrial fibrillation (AF) and non-alcoholic fatty liver disease (NAFLD) or metabolic-associated fatty liver disease (MAFLD) has been explored in recent cohort studies, however, the results have been controversial and inconclusive. This meta-analysis aimed to explore this potential association. Methods We systematically searched PubMed, Embase, and Web of Science databases to identify all relevant cohort studies investigating the association between NAFLD/MAFLD and AF published from database inception to October 30, 2022. Random-effects models were utilized to calculate hazard ratios (HRs) with 95% confidence intervals (CIs) for summary purposes. Additionally, subgroup and sensitivity analyses were performed. Results A total of 13 cohort studies with 14 272 735 participants were included. Among these, 12 cohort studies with 14 213 289 participants (median follow-up of 7.8 years) showed a significant association between NAFLD and an increased risk of incident AF (HR = 1.18, 95% CI: 1.12-1.23, P < 0.00001). Our subgroup analyses mostly yielded similar results, and the results of sensitivity analyses remained unchanged. However, meta-analysis of data from 2 cohort studies with 59 896 participants (median follow-up of 2.15 years) showed that MAFLD was not linked to incident AF (HR = 1.36, 95% CI: 0.63-2.92, P = 0.44). Conclusion Current evidence shows that NAFLD may be linked to a slightly higher risk of developing AF, particularly among Asian populations and those diagnosed with NAFLD using FLI criteria. Nevertheless, there is not enough evidence to support the proposed association between MAFLD and an increased risk of AF. To better understand this relationship, future studies should consider factors such as specific population, the severity of NAFLD/MAFLD, diagnostic methods of NAFLD and AF, and cardiometabolic risk factors. Systematic Review Registration https://www.crd.york.ac.uk/prospero, identifier CRD42022371503.